MODEL SISTEM INFORMASI SURAT PERINTAH TUGAS DAN SURAT PERINTAH PERJALANAN DINAS BERBASIS WEB (STUDI KASUS: AMIK INDONESIA) - Munawir Munawir; Rahmi Hajriyanti (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2021)
The purpose of the research is to build a website-based program model for the creation of a website-based information system for assignment warrants and official travel warrants. For the application development process using the waterfall model, and data flow diagrams are used for logical data flow diagrams to describe the system to be proposed. The conclusions from the results of this study are; 1) The official travel order information system at the AMIK Indonesia Campus was developed to facilitate the processing of SPPD information for staff so that it becomes more effective and efficient, and 2) The official travel order information system at the AMIK Indonesia Campus was developed web-based using PHP and Mysql as databases thus producing SPPD input forms, employee data input forms, provincial, district and SPPD reports.